Triptolide and celastrol loaded silk fibroin nanoparticles show synergistic effect against human pancreatic cancer cells. Issue 32 (7th August 2017) - Ding, Baoyue; Wahid, Md Arif; Wang, Zhijun; Xie, Chen; Thakkar, Arvind; Prabhu, Sunil; Wang, Jeffrey
Abstract : Novel combination of triptolide and celastrol loaded silk fibroin nanoparticles show synergistic anti-pancreatic cancer effect in vitro . Abstract : Pancreatic cancer is a lethal disease with a dreadful 5-year survival rate of only 5%. In spite of several treatment options, the prognosis still remains extremely poor. Therefore, novel therapy strategies with combinations of drugs are urgently required to combat this fatal disease. Triptolide (TPL) and celastrol (CL), two main compounds in traditional Chinese medicine isolated from Thunder God Vine, have a broad range of bioactivities including anticancer activity. Silk fibroin (SF), a naturally occurring protein with several unique properties, is an ideal carrier material. In this study, we prepared TPL and CL loaded silk fibroin nanoparticles (TPL-SFNPs and CL-SFNPs) by a modified desolvation method and evaluated their synergistic effects against human pancreatic cancer cells. Both SFNPs were characterized for particle size and zeta potential. The entrapment efficiency, drug loading, and drug release profiles were evaluated by HPLC. The cytotoxicity and synergistic effect of SFNPs were investigated in MIA PaCa-2 and PANC-1 human pancreatic cells. The results showed that the particle sizes of TPL-SFNPs and CL-SFNPs were 166.4 ± 4.6 nm and 170.4 ± 2.3 nm, with a mean zeta potential −27.2 ± 2.0 mV and −25.5 ± 2.57 mV, respectively. TPL-SFNPs and CL-SFNPs have a drug loading of 57.0 ± 4.7 μg mg −1 and 63.5 ± 3.8 μg mg −1 along with an encapsulation efficiency of 81.8 ± 2.8% and 87.0 ± 5.1%, respectively. Drug release studies revealed that a rapid release of the drugs from SFNPs was observed at pH 4.5 (lysosomal pH) and a delayed release was observed at pH 7.4 (plasma pH). TPL-SFNPs (IC50 3.80 and 4.75 nM) and CL-SFNPs (IC50 0.38 and 0.64 μM) were 2–3 fold more potent against MIA PaCa-2 and PANC-1 cells than free TPL (IC50 11.25 and 11.58 nM) and CL (IC50 0.84 and 1.23 μM). Furthermore, co-treatment with TPL-SFNPs and CL-SFNPs increased the growth inhibition of the same cells significantly in comparison with TPL-SFNPs or CL-SFNPs alone. Almost all combination index (CI) values, calculated using the CompuSyn software, were <1, suggesting that the growth inhibition effect of TPL-SFNPs in combination with CL-SFNPs was synergistic rather than additive, further suggesting that this novel combination may offer a potential treatment for pancreatic cancer.